δ13C and δ18O record of Stalagmite GL-S3 (middle) from the Golgotha Cave in southwest Western Australia - Pauline C Treble; Andy Baker; Nerilie J Abram; John C Hellstrom; Jagoda Crawford; Michael K Gagan; Andrea Borsato; Alan D Griffiths; Petra Bajo; Monika Markowska; Stacey Priestley; Stuart I Hankin; et al. (PANGAEA, 2022)
GolgothaCave_GLS3middle_stalagmite_O&C_isotopes: median depth, d18O and d13C values in VPDB for 4 to 21.5 mm. Chronology is that used for Treble et al (2022).
In: Treble, PC et al. (2022): Golgotha Cave stalagmite records 1 ka [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.941440